Choosing A Credit Card - Mary N. Harrison (EDIS)
It is smart to shop for a credit card as carefully as you shop for any major purchase. Perhaps you have received offers in the mail asking if you would like to open a credit card account. Frequently these offers say that you are or have been “pre-approved” and urge you to respond “before the offer expires.” How do you know which card offers you the best terms? This document is Fact Sheet FCS5038, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: March 1991. Revised: June 2005.